Las máscaras - PEREZ DE AYALA, Ramón (ESPASA CALPE ARGENTINA, 1944)
CONTENIDO : PEREZ GALDOS; BENAVENTE; VALLE-INCLAN; LINARES RIVAS; VILLAESPESA; MORANO; LOPE DE VEGA; SHAKESPEARE; IBSEN; WILDE; DON JUAN